1999
DOI: 10.1111/j.1530-0277.1999.tb04541.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Alcohol‐Metabolizing Enzymes in Relation to Alcoholic Chronic Pancreatitis in Japan

Abstract: Long-term consumption of large amounts of alcohol is the main cause of chronic pancreatitis. All heavy drinkers, however, do not contract chronic pancreatitis. Although genetic predisposition to alcoholism and alcoholic liver disease has been reported, genetic susceptibility to alcoholic pancreatitis is still a matter of debate. To determine the relation between genotypes of alcohol-metabolizing enzymes and chronic alcoholic pancreatitis, we examined genotype patterns of aldehyde dehydrogenase 2 (ALDH 2), alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 13 publications
2
29
3
1
Order By: Relevance
“…Thus, the rate of AcH production (i.e., the rate of ethanol oxidation) that has been shown to be significant in pancreatic acinar cells (Haber et al, 1998) should affect the development of alcoholic pancreatitis. This hypothesis is supported by human data, according to which alcoholic pancreatitis has been associated with ADH3*1 alleles in white subjects (Couzigou et al, 1991;Day et al, 1991) and ADH2*2 alleles in Asians (Chao et al, 1997;Matsumoto et al, 1996), but not with the ALDH2 polymorphism (Chao et al, 1997;Maruyama et al, 1999;Matsumoto et al, 1996).…”
Section: Chronic Pathological Effects Of Alcohol Drinkingmentioning
confidence: 55%
“…Thus, the rate of AcH production (i.e., the rate of ethanol oxidation) that has been shown to be significant in pancreatic acinar cells (Haber et al, 1998) should affect the development of alcoholic pancreatitis. This hypothesis is supported by human data, according to which alcoholic pancreatitis has been associated with ADH3*1 alleles in white subjects (Couzigou et al, 1991;Day et al, 1991) and ADH2*2 alleles in Asians (Chao et al, 1997;Matsumoto et al, 1996), but not with the ALDH2 polymorphism (Chao et al, 1997;Maruyama et al, 1999;Matsumoto et al, 1996).…”
Section: Chronic Pathological Effects Of Alcohol Drinkingmentioning
confidence: 55%
“…These include upper gastrointestinal tract cancers (Coutelle et al, 1997;Tanabe et al, 1999;Väkeväinen et al, 2000), cirrhosis (Poupon et al, 1992;Yamauchi et al, 1995), and pancreatitis (Maruyama et al, 1999). Of particular interest to New Zealand researchers are a group of such studies that have been conducted with aboriginal tribes from Taiwan (Chen et al, 1997;Cheng and Chen, 1995;Thomasson et al, 1994).…”
mentioning
confidence: 99%
“…While Kimura et al [58] concluded that genetic polymorphisms of the ALDH2 gene infl uence the risk of developing alcoholic pancreatitis (in Japanese patients), this was not confi rmed by Maruyama et al [60] in Japanese and by Frenzer et al [59] in Caucasian patients.…”
Section: Alcohol-metabolizing and Detoxifying Genesmentioning
confidence: 75%
“…A study from Taiwan published by Chao et al [57] hypothesized later on that there might be an association between the ADH2*2 gene and (acute) alcoholic pancreatitis. However, the data published for patients with chronic alcoholic pancreatitis are not conclusive: No correlation was found between ADH2 polymorphisms and chronic pancreatitis in Japanese patients by Kimura et al [58] , and in 71 Australian patients (of European origin) by Frenzer et al [59] , while an elevated risk for chronic alcoholic pancreatitis for different genotypes of ADH2 was demonstrated by Maruyama et al [60] . In conclusion, further studies are needed to clarify these discrepancies, but these polymorphisms do not appear to be the key cofactors for alcoholic pancreatitis.…”
Section: Alcohol-metabolizing and Detoxifying Genesmentioning
confidence: 89%